Elastic properties of long-period stacking ordered phases in Mg–Zn–Y and Mg–Ni–Y alloys: A first-principles study. (15th March 2020) - Guo, Yanlin; Luo, Qun; Liu, Bin; Li, Qian
Abstract: In order to understand the strengthening mechanism and achieve the rational properties regulation of long-period stacking ordered phases (LPSO) contained Mg alloys, thermodynamic stability, transformation energies and elastic properties of LPSO in Mg–Zn–Y and Mg–Ni–Y systems are investigated via first-principles calculations. 14H-type LPSO (14H) is predicted to be the stable phase. Furthermore, the transformation energies from other LPSO to 14H are small, implying their appearance as metastable phases in Mg alloys. All LPSO phases contribute to the strength increment, especially for 14H that has the maximum effect, uncovering the availability of the property regulation through LPSO design. Graphical abstract: Image, graphical abstract